Poison woman : figuring female transgression in modern Japanese culture - Marran, Christine L. (University of Minnesota Press, 2007)
Based on the lives and crimes of no less than twenty real women, dokufu (poison women) narratives emerged as a powerful presence in Japan during the 1870s. In Poison Woman, Christine L. Marran investigates this powerful icon, its shifting meanings, and its influence on defining womens sexuality and place in Japan.